Cultural responsiveness in applied behavior analysis: Research and practice. Issue 3 (12th April 2022) - Jimenez‐Gomez, Corina; Beaulieu, Lauren
Abstract : The new Ethics Code for Behavior Analysts requires that certificants engage in training related to culturally responsive service delivery (BACB, 2020). There is limited work in the area of culturally responsive evidence‐based practice within our field. Therefore, it is incumbent on researchers and practitioners to identify best practices for working with diverse populations. Hence, the purpose of this paper is three‐fold: a) to review research within and outside the field of ABA related to culturally responsive assessment and treatment and provide practice recommendations, b) to examine the extent to which current practices in behavior assessment and treatment align with aspects of culturally responsive practices, and c) to inspire research in the areas of behavior assessment and treatment to identify best practices with regard to culturally responsive behavior analytic practices. The content of this paper is grounded in the framework described by Beaulieu and Jimenez‐Gomez (2022).